Literature study: measuring banking performance in Indonesia due to policies for handling the covid-19 pandemic - Dahnil Anzar Simanjuntak; Andre Mirza Hartawan; Mochammad Yana Aditya (Institute of Computer Science (IOCS), 2023)
The Covid-19 pandemic, with its peak period in 2019-2021, has, directly and indirectly, affected banking performance in Indonesia. Many studies have been conducted with mixed results. Based on the results of previously published studies, this study seeks to see banking performance due to the Covid-19 pandemic. Using the literature review approach, the study gets 100 scientific articles from the database of international and national journal providers Google Scholar with the Publish or Perish 8 tool. Based on the selection of 100 research data obtained, as many as 55 selected articles. Selected articles are based on the relevance or suitability of the material. A total of 45 articles were not selected for several reasons, such as inappropriate material, no publisher/source found, and irrelevant research results. Findings of this study, the impact of the Covid-19 pandemic in Indonesia was classified into three: reducing performance, enhancing performance, and neutral or diverse.